Study on the Load Characteristics of the Planetary Gear Transmission System with Addendum Modification While Considering Errors - Xu Pengpeng; Chen Lifeng; Zhao Yingjun (Jixie chuandong)
A study on the load characteristics of the modified gear planetary gear systems is conducted to address the issue of uneven loads between planetary gears due to manufacturing and installation errors, which result in deviations between the radial and circumferential installation positions of planetary gears and non-offset values. Based on the theory of rotor dynamics, the time-varying stiffness and the radial and circumferential offsets of the planetary gears are considered, and the five-degree-of-freedom dynamic model of the planetary gear transmission system with addendum modification is established. The response and frequency spectrum of the system are solved by the Runge-Kutta method. The load distribution characteristics of the planet gears under different radial offsets, circumferential offsets, and comprehensive offsets are analyzed. The influence of the radial and circumferential offset of the planetary gear on the load distribution of the planetary gear transmission system is discussed, and the variation law of the load vibration amplitude of the planetary gear transmission system with addendum modification under the time and frequency is obtained. The simulation results show that the load characteristics of the planetary gear train considering the error are quite different from those in theory. Its vibration amplitude of the planetary gear transmission system is greatly affected by the radial offset, and the large radial offset has the greatest impact on the load of the planetary gear. Small deflections of the planetary gear during installation can lead to large changes in the load characteristics. The planetary gear transmission system load test platform is built, the frequency-doubling vibration response signal of the planetary reducer housing is tested, and the relation between the planetary gear transmission system load force and vibration response is obtained. The amplitude variation trend in the experimental results is similar to that in the simulation analysis, and the correctness of the established model and solution method is verified.